Strategi Pengembangan Ternak Kerbau Pada Sistem Pemeliharaan Semi Intensif di BPTU HPT Siborongborong - Rahma Fajar Damayanti; Fira Tantri Lazira; Ratih Aulia; Kiagus Muhammad Zain Basriwijaya (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Study was to emit various strategies to develop buffalo cattle in a semi-intensive rearing system at BPTU HPT Siborongborong. Primary data, collected through observation, focus group discussion (FGD), and secondary data, collected through relevant reports and literature. Development potential, challenges and opportunities were identified using desirability evaluation, descriptive analysis and SWOT. The results show that the semi-intensive system implemented has improved animal productivity, with adult buffaloes averaging 500 kilograms in weight and 0.7 kilograms in daily growth. The system also offers significant economic benefits, with an average net profit of IDR 800,000 for each head each month. However, a lack of protected human resources and seasonal forage shortages remain constraints. Feed diversification, farmer training and analysing the use of advanced technology are the plans made based on SWOT. The Siborongborong semi-intensive system has a great opportunity to become an example of effective and sustainable buffalo management in Indonesia.